Nine new species of Timonius (Rubiaceae) from Kinabalu Park, Borneo - Chen, Junhao; Wong, Khoon Meng; van Der Ent, Antony; Tan, Hugh Tiang Wah (Phytotaxa, 2014)
Nine new species of Timonius (Rubiaceae) from Kinabalu Park are described: T. abanii, T. beamanii, T. bullatus, T. kinabaluensis, T. leopoldii, T. ophioliticus, T. pannosus, T. stenolobus, and T. tambuyukonensis. Of the nine species, six are likely to be endemic to the Kinabalu massif, and four appear to occur exclusively on ultramafic soils.